THE COMPARISON OF ROAD DAMAGE VALUES BASED ON PCI (PAVEMENT CONDITION INDEX) METHOD OBSERVATION AND IRI (INTERNATIONAL ROUGHNESS INDEX) METHOD ON ROAD CLASS II IN LUMAJANG DISTRICT - Devita Sari; Sri Sukmawati; Akhmad Hasanuddin (Jurnal Rekayasa Sipil dan Lingkungan, 2019)
Roads are a means of transportation that is often used by Indonesians to travel. Some class II road segments in Lumajang Regency include Tempeh-Sumberjati, Sumberjati-Karangrejo, Karangrejo-Yosowilangun, and Jalan Lintas Timur. The four sections are collector roads outside the city so that large vehicles often pass. Before handling the road, it must first be assessed on the condition of the pavement. The road surface condition assessment system uses the PCI method and the IRI method. The purpose of this study was to determine the condition of road damage and handling damage to the road so that the maintenance category was obtained. The IRI method is obtained from the Bina Marga Lumajang PU, while the PCI method is done visually. The average results of the four PCI methods are 76.54 with very good conditions and the IRI method is obtained 3.94 with good conditions so that both of these methods produce the same conclusions Maintenance for the PCI method and the IRI method uses routine maintenance, seen from both values. Jalan merupakan sarana transportasi yang sering digunakan bagi warga Indonesia untuk berpergian. Beberapa ruas jalan kelas II di Kabupaten Lumajang antara lain Tempeh-Sumberjati, Sumberjati-Karangrejo, Karangrejo-Yosowilangun dan Jalan Lintas Timur. Keempat ruas tersebut merupakan jalan kolektor luar kota, sehingga sering dilewati kendaraan bermuataan besar. Sebelum dilakukan penanganan jalan, terlebih dahulu harus dilakukan penilaian kondisi perkerasan jalan. Sistem penilaian kondisi permukaan jalan menggunakan metode PCI dan metode IRI. Tujuan dari penelitian ini untuk mengetahui kondisi kerusakan jalan dan penanganan kerusakan jalan, sehingga didapatkan kategori pemeliharaan. Untuk metode IRI didapatkan dari PU Bina Marga Lumajang, sedangkan metode PCI dilakukan secara visual. Hasil rata-rata keempat ruas metode PCI sebesar 76,54 dengan kondisi sangat baik dan metode IRI didapatkan 3,94 dengan kondisi baik, sehingga kedua metode ini menghasilkan kesimpulan yang sama Pemeliharaan untuk metode PCI dan metode IRI menggunakan pemeliharaan rutin, dilihat dari kedua nilai.